Kontribusi Pendidikan Al-Islam Kemuhammadiyahan dalam Pembinaan Ibadah Siswa Di SMP Muhammadiyahan 57 Medan - Salmiah Salmiah (Yayasan Rahmat Islamiyah, 2023)
The purpose of this study is to see how Muhammadiyah Al-Islam Education contributes to the development of student worship and what are the problems in fostering worship. This type of research is qualitative with a descriptive approach and the data analysis technique in this study is descriptive analysis, namely data in the form of words, sentences or paragraphs that describe events that occur and uses three stages, namely data reduction, source triangulation and withdrawal conclusion. The sources in this study were school principals, Kemuhammadiyahan teachers and students of SMP Muhammadiyah 57 Medan, as well as data collection techniques through observation, interviews and documentation. Based on the results of the study it can be concluded that the contribution of Al-Islam Kemuhammadiyahan Education in cultivating student worship in the form of material understanding, motivation, thaharah method, prayer readings to student prayer movements must be in accordance with what was outlined by the Prophet Muhammad as exemplified as stated in Muhammadiyah tarjih. The obstacle in cultivating participant worship is the difficulty in providing understanding because not all students are from the Muhammadiyah organization.